2019
DOI: 10.1109/access.2019.2942393
|View full text |Cite
|
Sign up to set email alerts
|

OAR Dose Distribution Prediction and gEUD Based Automatic Treatment Planning Optimization for Intensity Modulated Radiotherapy

Abstract: In current knowledge-based treatment planning for intensity-modulated radiation therapy (IMRT), 3-dimensional dosimetric goals are predicted to provide abundant and appropriate starting points for planning optimization, but considering there're uncertainties with those dose distribution predictions, how to tailor the objective function and constraints accordingly is quite a concern. Here, we represent a novel automatic treatment optimization method that is capable of making the most of dose distribution predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Even though the gEUD is derived from a tissue-specific biological dose, a gEUD optimization object enables the exploration of large solution spaces and improves the sparing of normal tissue doses (Wu et al 2002) by reducing the trial and error required for optimization (Jia et al 2019). To simplify the OAR dose constraints for optimization, effective gEUD use for optimization is essential (Li et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the gEUD is derived from a tissue-specific biological dose, a gEUD optimization object enables the exploration of large solution spaces and improves the sparing of normal tissue doses (Wu et al 2002) by reducing the trial and error required for optimization (Jia et al 2019). To simplify the OAR dose constraints for optimization, effective gEUD use for optimization is essential (Li et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…2.3. Optimization process from gEUD deviation perspective Single a-value gEUD optimization with a changed a-value in the phantom and patient cases has been widely reported (Wu et al 2002, Thieke et al 2003, Hartmann and Bogner 2008, Li et al 2012, Liang et al 2016, Feng et al 2017, Fogliata et al 2018, Jia et al 2019. Specifically, Fogliata et al reported their results using a phantom considering the Eclipse PO gradient solver for optimization.…”
Section: Outline Of This Study: Geud Curve Deviation Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially for cancer radiotherapy surgery, it requires that the radiation can precisely cover the tumor cells while avoiding excessive damage to normal tissues. However, in clinical practice, factors such as respiration, digestion, postural changes, and instrument disturbances may cause unintended movements of target organs and even cause tumors to leave the planned target volume (PTV) range [2][3][4], resulting in tumor remnants. And also expose a large amount of healthy tissues to the radiation range, causing inevitable unnecessary damage or even serious side effects.…”
Section: Introductionmentioning
confidence: 99%